1994
DOI: 10.1055/s-2008-1046623
|View full text |Cite
|
Sign up to set email alerts
|

Schwere renale Methotrexat-Ausscheidungsstörung nach Hochdosis-Therapie

Abstract: Even in patients with normal renal function, high-dose methotrexate therapy (HDMTX) may be followed by extremely prolonged MTX elimination through alkaline diuresis is performed correctly. By inquiry in Germany, Austria and Switzerland for HDMTX infusions with MTX plasma concentration 42 h after start of exposure (MTX-42) higher than 5 mumol/l (microM), we analyzed data from 21 patients in whom impairment of renal methotrexate elimination had received 5 g/m2.24h, 3 had received 12 g/m2.4h. They presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…14 However, reports of significant morbidity and mortality secondary to HDMTX-induced renal dysfunction have continued to appear in the literature. 11,[15][16][17][18][19] Because there is no centralized reporting mechanism for MTX nephrotoxicity, to our knowledge the current incidence of HDMTX-induced renal dysfunction is unknown.…”
mentioning
confidence: 99%
“…14 However, reports of significant morbidity and mortality secondary to HDMTX-induced renal dysfunction have continued to appear in the literature. 11,[15][16][17][18][19] Because there is no centralized reporting mechanism for MTX nephrotoxicity, to our knowledge the current incidence of HDMTX-induced renal dysfunction is unknown.…”
mentioning
confidence: 99%
“…The excretion of MTX is influenced by many factors such as age, the hydration status and the concurrent use of nephrotoxic agents [2]. Furthermore, it has been reported that delayed MTX excretion may occur in the absence of any predisposing factor [5,10,11], and in our cases, the reason for delayed MTX excretion was not determined. However, we surmise that a young age or a small body size might have contributed to its development.…”
Section: Discussionmentioning
confidence: 74%
“…However, the factors that predisposed the patients to delayed MTX excretion were unclear in these cases. A reduced effective blood volume or the concurrent use of nephrotoxic agents are known to be related to the development of delayed MTX excretion [5,6], but neither patient had signs of decreased blood volume nor they were concurrently receiving any nephrotoxic agent [7]. Furthermore, the previous courses of HD MTX in case 2 and the following chemotherapy (case 1) were uneventful.…”
Section: Discussionmentioning
confidence: 99%
“…It consists frequently on a nonoliguric renal failure which generally disappears in two to three weeks [12][13][14]. Some patients may develop nausea, vomiting or diarrhea as prodroms [14,15]. Urine alkalinization and leucoverin rescue are the cornerstones of the management of the earlier signs of renal dysfunction.…”
Section: Renal Toxicitymentioning
confidence: 99%